INSTALASI LISTRIK MASJID AL-IKHLAS KAMPUNG KARET-BATU BESAR KECAMATAN NONGSA KOTA BATAM - Hadiyanto, Gunawan Toto; Mardiono, Djoko Anwar; Apriyanto, Bambang; Nurhatisyah; Effendy, Nur Effendi (Jurnal Pendekar Nusantara, 2023)
The people of Kampung Karet, Nongsa District, most of them still don't understand about electrical installations, the condition of the electrical installation system in people's homes and especially places of worship (mosques) are still many that do not comply with general regulations regarding electrical installations. Apart from that, there are still many connections. -connection of electrical installations carried out by the community itself which does not comply with regulations. Community service by providing counseling and going directly to see the location that is the target of carrying out service activities, namely the Al-Ikhlas mosque. By holding community service (PKM), the residents of Rubber Village will understand how to install electricity properly, correctly and safely. The equipment selected for installation in an electrical installation must meet applicable standards and must be suitable for its environment. Installation of equipment must comply with the provisions in PUIL, and match the equipment manufacturer's instructions. Electrical installations must be regularly inspected and tested for misuse, damage or poor installation, including loose connections. To protect against leakage currents, an ELCB can be installed. In order to achieve an increase in public knowledge and understanding about the importance of electrical hazards, this activity needs to be sustainable.